Carbohydrate Hydrolysis by Glycosidase : Mechanistic Aspects and Applications - จิตอ่อนน้อม จิตระยุทธ์ (KKU Science Journal, 2013)
Recent studies of the carbohydrate hydrolysis by glycosidase (GH) have shown that a number of GH families undergo various unusual mechanisms, which differ from the known classical mechanisms, including substrate-assisted catalysis, exogenous bases, alternative nucleophiles and NAD-dependent hydrolysis. The main reason for such specific mechanisms is the diversity of key amino acids, which function as a catalytic base/nucleophile. Mutation of the catalytic base/nucleophile can have a profound impact on substrate specificity, producing enzymes with new function roles and better activity. This principle can be applied in protein engineering for the design and synthesis of proteins with specific properties and high efficiency. Gaining the knowledge of GH mechanism, especially the catalytic diversity, is thus crucial and has been updated in this review.